Assessment of Left Ventricular Structural Remodelling in Patients with Diabetic Cardiomyopathy by Cardiovascular Magnetic Resonance - Yongning Shang; Xiaochun Zhang; Liu Chen; Weiling Leng; Xiaotian Lei; Qi Yang; Ziwen Liang; Jian Wang (Journal of Diabetes Research, 2016)
Background. Diabetic cardiomyopathy (DCM) is always accompanied with alteration of left ventricular structure and function. The aims of this study were to assess the structural remodelling in patients with DCM by cardiovascular magnetic resonance (CMR) and correlation of structural remodelling with severity of DCM. Methods. Twenty-five patients (53.8±8.8 years, 52.0% males) with DCM and thirty-one normal healthy controls (51.9±13.6 years, 45.2% males) were scanned by CMR cine to assess function and structure of left ventricular. Length of diabetic history and results of cardiac echocardiography (E′, A′, and E′/A′) were also measured. Results. Compared with normal controls group, DCM group was associated with significantly increased ratio of left ventricular mass at end diastole to end-diastolic volume (MVR) (P<0.05) and no significant difference was in mass at end diastole (P>0.05). The ratio correlated with both length of diabetic history and echocardiographic Doppler tissue imaging E′ (all P<0.05). Conclusions. CMR can be a powerful technique to assess LV remodelling, and MVR may be considered as an imaging marker to evaluate the severity of LV remodelling in patients with DCM.